Efficacy of injection with triamcenolone acetonide proximal to the carpal tunnel in relieving symptoms of carpal tunnel syndrome: a randomised control trial - Islam, Monirul; Hakim, Maliha; Hasan, Suzon Al (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3870 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):43-45